Primary Surpluses and sustainable Debt Levels in Emerging Market Countries - Ostry, Jonathan; Abiad, Abdul (Washington, D.C. : International Monetary Fund, 2005)
This paper aims to put some constraints on the way primary surpluses are projected when making assessments of public debt sustainability. Projections should be tied either to the country's historical track record in generating surpluses-if the institutional and other factors accounting for this track record are expected to persist-or to some model that links primary surpluses to their fundamental determinants, either on the basis of constant institutions and policies or a credible reform program. History-based or model-based primary surplus projections provide a useful benchmark for judging the realism of fiscal forecasts underlying debt sustainability calculations. Together with information on future growth and interest rates, the primary surplus projections can be used to generate measures of overborrowing, and the magnitude of adjustment needed to return debt to a sustainable level.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet